Puisi Prosais Pesantren: Diksi Arab, Simbolisme Islam, dan Representasi Takdir - Rokib, Mohammad; Kisyani, Kisyani; Rohaedi, Diding Wahyudin; Rengganis, Ririe; Indrawati, Dianita (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2024)
This study examines prosaic poetry of pesantren, focusing on the use of Arabic diction, Islamic symbolism, and the concepts of destiny and divine will in Islamic-sense poetry or literature. The research aims to understand how these elements shape aesthetics and meaning in prosaic poetry written by teachers at Madrasah Bertaraf Internasional (MBI) Pesantren Amanatul Ummah. Using a qualitative approach, the study analyzes a collection of prosaic poetry produced during a creative writing workshop. The findings reveal that Arabic diction functions not only as a linguistic element but also as an Islamic identity marker. Islamic symbolism in poetry reflects writers’ religious experiences, while the concepts of destiny and divine will highlight spiritual reflections in their works. This study contributes to contemporary Islamic literary studies and offers new perspectives on the relationship between literature, language, and religious values within the pesantren educational context.